2017
DOI: 10.1002/jhet.2853
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Anticancer Activity of 3H–benzo[f]chromen‐3‐one Derivatives

Abstract: A series of substituted aminomethylbenzocoumarin derivatives 8a-i have been synthesized, characterized, and structure of compound 8g was confirmed by X-ray single crystal analysis. All the synthesized compounds were tested for their anticancer activity against cancer cell lines A549 (lung carcinoma cell line), MCF7 (breast cancer cell line), and A375 (melanoma cell line). Compounds 8a, 8f, and 8h showed excellent growth inhibitory activity against all three cell lines, respectively. Compounds 8a and 8f were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…A series of substituted aminomethyl benzocoumarin derivatives was synthesized and tested for their anticancer activity against the A549, MCF7, and A375 cancer cell lines. 192 Among them, the anilinocoumarin compound 122 ( Fig. 120 ) showed excellent growth inhibitory activity against the A549, MCF7, and A375 cancer cell lines with IC 50 values of 4.29 μM, 5.17 μM, and 9.02 μM, respectively.…”
Section: Coumarin Hybridsmentioning
confidence: 99%
“…A series of substituted aminomethyl benzocoumarin derivatives was synthesized and tested for their anticancer activity against the A549, MCF7, and A375 cancer cell lines. 192 Among them, the anilinocoumarin compound 122 ( Fig. 120 ) showed excellent growth inhibitory activity against the A549, MCF7, and A375 cancer cell lines with IC 50 values of 4.29 μM, 5.17 μM, and 9.02 μM, respectively.…”
Section: Coumarin Hybridsmentioning
confidence: 99%
“…The benzochromene structure is found in many natural products isolated from plants [ 4 , 5 , 6 , 7 , 8 ], lichens and fungi [ 9 ], and a wide range of biological activities such as antibacterial [ 5 , 10 ], antioxidant and anticancer activities have been reported for natural benzochromenes [ 9 , 11 ]. They have been reported to be able to intercalate with DNA [ 11 , 12 ], and to bind selectively to the estrogen receptor ERβ [ 13 ]. Several cannabinoids are benzochromenes and bind to the cannabinoid receptors CB1 and CB2 [ 5 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…A 3 H -benzo[f]chromen-3-one derivative, compound 4 , developed by Soni et al, showed efficacy against MCF-7 cells, with an IC 50 value of 0.83 µM. The analysis of the structure–activity pattern revealed the importance of the piperidine ring linked to the coumarin in the anti-breast cancer activity of the structure, whereas the replacement of the piperidine ring with phenyl or piperazine led to a decrease in potency [ 66 ]. Similarly, the 3-(3-oxosubstitutedphenyl-3-)4-(2-(piperidinyl)ethoxy)phenyl)propyl)-2 H -chromen-2-one derivative (compound 5 ) developed by Dube et al showed efficacy against MCF-7 cells, with an IC 50 value of 0.231 µM.…”
Section: Synthetic Coumarin-inspired Derivatives With Anti-breast Can...mentioning
confidence: 99%